The METTL3/MALAT1/PTBP1/USP8/TAK1 axis promotes pyroptosis and M1 polarization of macrophages and contributes to liver fibrosis - Bo Shu (Nature Publishing Group, 2021)
Abstract Pro-inflammatory M1 macrophages, via activating hepatic stellate cells, contribute to liver fibrosis. In this study, we examined the mechanism and the significance of a signaling axis, METTL3/MALAT1/PTBP1/USP8/TAK1, in regulating pyroptosis and M1 polarization of hepatic macrophages. Liver fibrosis model was established in vivo by CCl4 treatment; M1 polarization was induced in vitro by treating macrophages with lipopolysaccharide or interferon γ. Expressions of METTL3, MALAT1, PTBP1, USP8, and TAK1 were measured by RT-PCR and/or Western blot in Kupffer cells (KCs) isolated from in vivo model or in vitro activated macrophages. Macrophage phenotypes including inflammation (RT-qPCR analysis of a panel of proinflammatory cytokines and ELISA on productions of interleukin (IL)−1β and IL-18) and pyroptosis (Western blot of NLRP3, Caspase-1, and GSDMD) were investigated. The impact of METTL3 on m6A methylation of MALAT1 was examined by methylated RNA immunoprecipitation (RIP), the interaction between PTBP1 and MALAT1 or USP8 mRNA by combining RNA pull-down, RIP, and RNA stability assays, and the crosstalk between USP8 and TAK1 by co-immunoprecipitation and protein degradation assays. Functional significance of individual component of METTL3/MALAT1/PTBP1/USP8/TAK1 axis was assessed by combining gain-of-function and loss-of-function approaches. In KCs isolated from in vivo liver fibrosis model or in vitro M1-polarized macrophages, METTL3 was up-regulated, and sequentially, it increased MALAT1 level via m6A methylation, which promoted USP8 mRNA degradation through the interaction with PTBP1. Reduced USP8 expression regulated the ubiquitination and protein stability of TAK1, which promoted pyroptosis and inflammation of macrophages. The signaling cascade METTL3/MALAT1/PTBP1/USP8/TAK1, by essentially stimulating pyroptosis and inflammation of macrophages, aggravates liver fibrosis. Therefore, targeting individual components of this axis may benefit the treatment of liver fibrosis.